Structural reforms to enhance the sustainability and intergenerational equity of the National Pension System - Kank Koo Lee (KDI Journal of Economic Policy, 2024)
This paper examines reform measures for the National Pension System, analyzing their fiscal impacts. Despite past reforms adjusting contribution and replacement rates, the system faces ongoing sustainability challenges. We forecast that the reserve fund, peaking at 1,972.0 trillion KRW in 2039, will be depleted by 2054. A scenario analysis suggests that raising the contribution rate from 9% to 18% would extend solvency but not maintain long-term stability under the current DB structure, which promises benefits that exceed contributions. This highlights the difficulty of sustaining the fund through rate increases alone. This paper proposes a structural shift to a new cohort-based DC system ("New Pension"), which would provide benefits based on contributions and investment returns, avoiding depletion even with low birth rates. Under this plan, the "Old Pension" deficit would be supported by government funds, ensuring all generations receive at least their contributions back. For the Old Pension, the shortfall is projected to be 609 trillion KRW if limited to contributions through 2023, rising to 869 trillion KRW if extended to 2028. These results stress the importance of early reforms to ease the fiscal burden.
Keywords: H55; H68; I38; 330; Structural Reforms; National Pension System; Defined Contribution; Separation of Old/New Pension Systems